Comprehensive Curative Effect of Targeting PD-1 or Traditional Single-Agent Chemotherapy in Second-Line Therapy for Terminal or Metastatic Esophageal Cancer: A Systematic Review and Meta-Analysis - Wang, Yidan; Yang, Qiuxing; Liu, Jia; Shen, Xiying; Tai, Guomei; Gu, Hongmei (Journal of oncology, 2022)
The number of programmed cell death protein 1 (PD-1) inhibitors is gradually increasing; this study aimed to comprehensively and systematically evaluate the impact of PD-1 inhibitors as second-line therapy for terminal or metastatic esophageal cancer (EC) on patient survival and the occurrence of adverse events. Suitable randomized controlled trials (RCTs) were retrieved from PubMed, Web of Science, Embase, and Cochrane Library databases. Moreover, we searched for conference abstracts from the American Society of Clinical Oncology (ASCO) and the European Society for Medical Oncology (ESMO) to compare the comprehensive curative effects of PD-1 inhibitors or single-agent therapy in terminal or metastatic EC. The primary outcome indicators were overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR). Treatment-related adverse events (TRAEs) were the secondary outcome indicators. We compared the previously mentioned indicators of the two treatment modalities using Stata software (version 12.0). We compared the long-term survival rates of both treatment groups and analyzed the possible factors affecting OS. We selected five RCTs with 2197 patients as study subjects. Compared with conventional single-agent chemotherapy, PD-1 inhibitors greatly improved the patients’ OS (HR = 0.77, 95% CI 0.70–0.85, P<0.001), but PFS (HR = 0.93, 95% CI 0.77–1.12, P=0.431) and DCR (RR = 0.93, 95% CI 0.71–1.22, P=0.609) were not greatly improved. Moreover, PD-1 inhibitors improved ORR (RR = 1.83, 95% CI 1.16–2.89, P=0.009) and decreased TRAEs (RR = 0.76, 95% CI 0.61–0.95, P<0.001) and serious TRAEs (RR = 0.40, 95% CI 0.32–0.49, P<0.001). Further analysis demonstrated that OS was affected by age, sex, region, smoking history, and the number of organ and lymph node metastases. Compared with the traditional single chemotherapy drugs, PD-1 inhibitors can achieve higher OS and ORR, fewer and more serious TRAEs, and better efficacy and safety for second-line therapy of terminal or metastatic EC.